1991
DOI: 10.5014/ajot.45.2.156
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Occupational Therapy Curricula on Students’ Attitudes Toward Persons With Disabilities

Abstract: The influence of occupational therapy curricula on students' attitudes toward persons with disabilities was studied. Twenty-six female students in either their first or fourth (i.e, final) semester of the occupational therapy curriculum were assessed with the Attitudes Toward Disabled Persons Scale (ATDP) (Yukor, Block, & Younng, 1966). A comparison group, 26 female students in either their first or fourth semester of the medical technology program, was also assessed with this scale. As hypothesized, the fourt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 5 publications
5
31
0
1
Order By: Relevance
“…occupational therapy students) towards inclusion will determine why and how occupational therapy services are implemented within inclusive environments. As suggested in previous literature (Benham, 1988;Estes, Deyer, Hansen & Russell, 1991;Eagly & Chaiken, 1993;Lee, Paterson & Chan, 1994), the attitudes of occupational therapists and occupational therapy students towards inclusion may also play a significant role in the therapeutic relationship with students with disabilities.…”
Section: Introductionmentioning
confidence: 88%
“…occupational therapy students) towards inclusion will determine why and how occupational therapy services are implemented within inclusive environments. As suggested in previous literature (Benham, 1988;Estes, Deyer, Hansen & Russell, 1991;Eagly & Chaiken, 1993;Lee, Paterson & Chan, 1994), the attitudes of occupational therapists and occupational therapy students towards inclusion may also play a significant role in the therapeutic relationship with students with disabilities.…”
Section: Introductionmentioning
confidence: 88%
“…For example, one study identified that creativity, enjoying variety, being people-oriented and having a preference for practical or applied rather than academic course work were qualities that many occupational therapy students possessed (Madill, Macnab, & Brintnell, 1989). In addition, it has been found that, while undesirable characteristics such as poor knowledge and negative attitudes may be present in beginning students, these may improve during a course (Estes, Deyer, Hansen, & Russell, 1991;Lee, Paterson, & Chan, 1994). In this longitudinal study, we aim to examine the development of attitudes throughout the education programme, and to describe the 'socialization' of students into occupational therapy culture.…”
Section: Attitudes Of Occupational Therapy Studentsmentioning
confidence: 96%
“…The questionnaire used in this study was based on one used previously at the University of Queensland to identify factors influencing students' choice of veterinary science as a career, and their attitudes and career expectations (Heath, Western, & Makkai, 1985). The original questionnaire was modified for use with occupational therapy students.…”
Section: Instrumentmentioning
confidence: 99%
“…[18,[22][23][24] Similarly, a study on occupational therapy students reported that they were positively influenced towards persons with disabilities after having contact with disabled persons through fieldwork. [25] Furthermore, a multicentre university programme that surveyed 456 students from various departments reported that they developed less stigmatising attitudes after a course on mental illness. [26] However, not all healthcare students exhibit this positive attitude towards mental illness.…”
Section: Discussionmentioning
confidence: 99%